2019
DOI: 10.1021/acsomega.9b00296
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Preliminary Biochemical and Biological Studies of [RuCl(p-cymene)(N,N-bis(diphenylphosphino)-isopropylamine)][BF4] in Breast Cancer Models

Abstract: Breast cancer is the second leading cause of cancer death worldwide. Despite progress in drug discovery, identification of the correct population is the limiting factor to develop new compounds in the clinical setting. Therefore, the aim of this study is to evaluate the effects of a new metallodrug, [RuCl( p -cymene)( N , N -bis(diphenylphosphino)-isopropylamine)][BF 4 ] ( pnpRu-14 ), as a lead pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Anti-tumor effects when found in essential oils from Nigella sativa [295]. Ruthenium 11 (p-Cymene) complexes were effective and selective against several cancers [296][297][298].…”
Section: Compound In Vitro Effects In Vivo Effects Clinical Trials P-mentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-tumor effects when found in essential oils from Nigella sativa [295]. Ruthenium 11 (p-Cymene) complexes were effective and selective against several cancers [296][297][298].…”
Section: Compound In Vitro Effects In Vivo Effects Clinical Trials P-mentioning
confidence: 99%
“…p-Cymene is a common ligand for ruthenium, proposed as a potential alternative to platinum-based chemotherapies. Ruthenium II (p-Cymene) complexes have been suggested as effective and selective anticancer candidates under various forms for different cancer types [296][297][298].…”
Section: P-cymenementioning
confidence: 99%
“…In a previous study, we reported Ru0 as the lead PNP-Ru compound by preliminary biochemical and biological studies in different breast cancer subtypes [37]. The results showed that complex Ru0 is much more effective in promoting in vitro cytotoxic effect on HER2+ and RH+/HER2− breast cancer cell lines than the reference metallodrugs cisplatin, carboplatin, or RAPTA-C [35].…”
Section: Antiproliferative Efficacy Of New Synthetized Ruthenium Compounds Compared To Ru0 and Platinsmentioning
confidence: 94%
“…On the basis of the cytotoxic results of Ru3 in breast cancer cell lines, the mechanism of cell death induction was evaluated. We analyzed Ru3 ability to induce apoptosis by flow cytometry as previously described [37,53,[55][56][57]. The experiments were performed using an incubation time of 48 h, and Ru3 concentrations corresponding to their respective IC 50 value.…”
Section: Ru3 Exerts Apoptotic-based Cell Death In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation